Deterrent Effect of Curfew Enforcement: Operation Nightwatch in St. Louis, 2003-2005 - Urban, Lynn S. ([Verlag nicht ermittelbar], 2005)
This study was conducted between December 2003 and January 2005, to determine if the curfew check program in St. Louis, Missouri, known as Nightwatch, was meeting its stated goals of reducing recidivism and victimization among juvenile offenders. The study was conducted using a pretest and two post-tests on an experimental group and a comparison group. The pretest (Time 1) was given to 118 juveniles. The first post-test (Time 2) was completed by 78 juveniles and the second post-test (Time 3) was completed by 37 juveniles. The tests were designed to measure the respondents' perceptions of certainty of punishment, as well as to measure their out of home activities. Important variables included in the study are levels of parental supervision, self-reported behaviors of the juvenile respondent, perceived severity of punishments, measures of impulsiveness, and self-reported victimization of the respondent, as well as variables related to the Nightwatch program, including the number of visits, sanctions or rewards received by the respondent.